Gastric Ulcer Healing Property of Bryophyllum pinnatum Leaf Extract in Chronic Model In Vivo and Gastroprotective Activity of Its Major Flavonoid - Edilane Rodrigues Dantas De Araújo; Gerlane Coelho Bernardo Guerra; Anderson Wilbur Lopes Andrade; Júlia Morais Fernandes; Valéria Costa Da Silva; Emanuella De Aragão Tavares; Aurigena Antunes De Araújo; Raimundo Fernandes de Araújo Júnior; Raimundo Fernandes de Araújo Júnior; Raimundo Fernandes de Araújo Júnior; Raimundo Fernandes de Araújo Júnior; Silvana Maria Zucolotto; et al. (Frontiers Media S.A., 2021)
Gastric ulcer is a common disease that develops complications such as hemorrhages and perforations when not properly treated. Extended use of drugs in the treatment of this pathology can provoke many adverse effects. Therefore, finding medicinal plants with gastroprotective and mucosal healing properties has gained increasing interest. Bryophyllum pinnatum (Crassulaceae), popularly known in Brazil as "saião" or "coirama," has been used to treat inflammatory disorders. It is rich in flavonoids, and quercetin 3-O-α-L-arabinopyranosyl-(1→2)-O-α-L-rhamnopyranoside-Bp1 is its major compound. In this study, we aimed to investigate ulcer healing properties of B. pinnatum against an acetic acid-induced chronic ulcer model and the gastroprotective activity of Bp1 against gastric lesions induced by ethanol and indomethacin. Ultrafast liquid chromatography was used to quantify the main compounds (mg/g of the extract)-quercetin 3-O-α-L-arabinopyranosyl-(1→2)-O-α-L-rhamnopyranoside (33.12 ± 0.056), kaempferol 3-O-α-L-arabinopyranosyl-(1→2)-O-α-L-rhamnopyranoside (3.98 ± 0.049), and quercetin 3-O-α-L-rhamnopyranoside (4.26 ± 0.022) and showed good linearity, specificity, selectivity, precision, robustness, and accuracy. In vivo studies showed that treatment with the extract at 250 and 500 mg/kg stimulated the healing process in the gastric mucosa with significant ulceration index reduction, followed by improvement in the antioxidant defense system [increased glutathione (GSH) levels, decreased superoxide dismutase upregulation, and malondialdehyde (MDA) levels]. Moreover, the extract decreased interleukin-1β and tumor necrosis factor-a levels and myeloperoxidase (MPO) activity, increased interleukin 10 levels, showed a cytoprotective effect in histological analyzes and also downregulated the expression of cyclooxygenase-2 and NF-κB (p65). The pretreatment with Bp1 at a dose of 5 mg/kg reduced gastric lesions in the ethanol and indomethacin models, increased GSH, and decreased MDA levels. In addition, the pretreatment decreased MPO activity, interleukin-1β and tumor necrosis factor-α levels, while also showing a cytoprotective effect in histological analyzes. Our study suggests that treatment with B. pinnatum extract showed a higher inhibition percentage than pretreatment with the Bp1. This might in turn suggest that Bp1 has gastroprotective activity, but other compounds can act synergistically, potentiating its effect. We conclude that B. pinnatum leaf extract could be a new source of raw material rich in phenolic compounds to be applied in food or medicine.